2015
DOI: 10.1037/a0038544
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotion regulation and cognitive control in the association between mindfulness disposition and stress.

Abstract: Dispositional mindfulness is associated with lower levels of perceived stress, with increased emotional regulation and cognitive control proposed as mechanisms underlying these stress-buffering effects of mindfulness. Within aging, these controlled processes represent paradoxically divergent trajectories such that older adults exhibit reduced cognitive control capacities, while emotional regulation abilities are well maintained, and at times enhanced. Our study seeks to examine the role of emotional regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 57 publications
6
69
0
5
Order By: Relevance
“…), which has been correlated with reduced stress perception across stages of adulthood (Prakash et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), which has been correlated with reduced stress perception across stages of adulthood (Prakash et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, these data suggest that these differences arise from individual specific genetic and/or environmental effects, and that sibling shared genetic and environmental factors are not predisposing in this manner. Other evidence also contradicts this interpretation, as relatively decreased cortical thickness in the DLPFC (including within the RMFG) in adolescent females has been associated with decreased cognitive reappraisal, a form of emotion regulation (Vijayakumar et al 2014), which has been correlated with reduced stress perception across stages of adulthood (Prakash et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, those individuals who rated themselves as more mindful, i.e. had greater 'dispositional mindfulness', generally report lower levels of perceived stress (Prakash et al, 2015). This is important because the level of stress is strongly related to physical and mental health as well as cortical thinning.…”
Section: Neural Basis Of Mindfulness Interventions That Moderate the mentioning
confidence: 99%
“…(22,(27)(28)(29) Other studies have also reported the potential effects of mindfulness on inhibitory control (i.e. the ability to override more dominant or automatic responses), cognitive flexibility (the ability to switch between tasks or sets of rules, also referred to as attentional switching) (23)(24)(25)27,(30)(31)(32) and speed of processing (the speed at which a person performs a cognitive activity), (22,33,34) despite other contradictory findings. (35) However, the mixed results could reflect methodological, training or sample differences.…”
Section: Introductionmentioning
confidence: 99%
“…(19,20) This is due to the reciprocal connections between attention and working memory (21) as well as better emotional regulation and the inhibition of secondary elaboration of thoughts. (19,(22)(23)(24)(25) Working memory is a limited-capacity system, where information is temporarily stored and manipulated. (26) An improvement in sustained attention following mindfulnessbased stress reduction was found in some studies, but not in others.…”
Section: Introductionmentioning
confidence: 99%